The Growth Rate of Cyphastrea Coral Fragment Under Controlled Condition - Reynaldi Surya Putra; Adrian Rahman Septiandi; Riyanti Riyanti (Jurnal Biologi Tropis, 2023)
The role of corals was very important in coastal and marine ecosystems, whether in terms of education, ecology, and socio-economy. Coral growth can be used as an indicators of marine ecosystem health. This study was aimed to observed survival rate and the growth rate of Cyphastrea coral fragments. Cyphastrea coral fragments growth rate was observed in ex-situ sites and was conducted over a period of 3 months. The micro-fragmentation method was applied in this study. Several factors such as water temperature, light levels, and nutrient concentrations were measured and controlled throughout the study. The growth rate of Cyphastrea coral fragments was measured using ImageJ software. Result of this study exhibited that survival rate of Cyphastrea was 100% and the growth rate of Cyphastrea was 0.012 cm2/month. This study provides important information on the factors that affect the growth rate of Cyphastrea coral fragments in ex-situ sites. The result of this study can be used to develop more effective strategies for coral reef restoration.